Gene target discovery with network analysis in Toxoplasma gondii - Alonso, Andrés Mariano (2019)
Infectious diseases are of great relevance for global health, but needed drugs and vaccines have not been developed yet or are not efective in many cases. In fact, traditional scientifc approaches with intense focus on individual genes or proteins have not been successful in providing new treatments. Hence, innovations in technology and computational methods provide new tools to further understand complex biological systems such as pathogen biology. In this paper, we apply a gene regulatory network approach to analyze transcriptomic data of the parasite Toxoplasma gondii. By means of an optimization procedure, the phenotypic transitions between the stages associated with the life cycle of T. gondii were embedded into the dynamics of a gene regulatory network. Thus, through this methodology we were able to reconstruct a gene regulatory network able to emulate the life cycle of the pathogen. The community network analysis has revealed that nodes of the network can be organized in seven communities which allow us to assign putative functions to 338 previously uncharacterized genes, 25 of which are predicted as new pathogenic factors. Furthermore, we identifed a small gene circuit that drives a series of phenotypic transitions that characterize the life cycle of this pathogen. These new fndings can contribute to the understanding of parasite pathogenesis.